Sustainability performance reporting : a technocratic shadowing and silencing - Journeault, Marc; Levant, Yves; Picard, Claire-France (Critical Perspectives on Accounting, 2020)
Global Reporting Initiative (GRI) guidelines have become the most relevant institution in sustainability reporting standards, highly adopted by organizations worldwide. However, much criticism has been raised about these standards’ ability to further sustainable development within organizations and render their sustainability performance more accountable and transparent. Using a case study of Hydro-Québec, an important hydro-electricity provider in Quebec, Canada, and its relationship with the Cree, an Indigenous community, the purpose of this study is to provide theoretical and empirical insights on the subject by showing how GRI guidelines, legitimized and reinforced through their institutionalization, tend to create a limited scope and an incomplete picture of the organization’s sustainability performance reporting. More specifically, this paper highlights two main problems arising from the use of these standards. First, drawing on the ideology of numbers of Chelli and Gendron (2013), this paper examines how GRI technocratic guidelines frame the sustainability reporting discourse, thereby contributing to leaving aspects of organizational sustainability performance in the shadows. Second, drawing on the ontological typology of Descola (2013), this study examines how these guidelines are ontologically driven by a Western view of nature. This contributes to silencing alternative ontologies in organizational sustainability performance reporting.